Implementasi Projek Penguatan Profil Belajar Pancasila Dalam Pembelajaran IPS: (Penelitian Deskriptif-Kualitatif di SMP Negeri 6 Kota Balikpapan pada Pembelajaran IPS di kelas VII Tahun Ajaran 2023/2024) - Simanjuntak, Devi Sapnanda Alfiyyah (The Indonesian Journal of Social Studies, 2024)
The Pancasila Student Profile is a program designed to strengthen students' character in various life contexts. The Pancasila Student Profile Strengthening Project (P5) is a forum for implementing the Pancasila Student Profile in improving students' character in learning. In its implementation, there are several problems such as difficulties in planning, determining themes and modules, differences in student attitudes and characters, availability and readiness of facilitators, limited facilities and infrastructure, and finding their relationship with social studies learning. Therefore, this study aims to evaluate the implementation of the Pancasila Student Profile Strengthening Project (P5) at SMP Negeri 6 Balikpapan City in social studies learning for class VII in the 2023/2024 academic year. The objectives include planning, implementation, evaluation, and identification of supporting and inhibiting factors in the implementation of P5 in the school. The method used is descriptive with a qualitative research approach. The results of this study are that in the planning stage, SMP Negeri 6 Balikpapan City has followed the P5 guidelines well, although problems such as time allocation, module preparation, and problems with the facilitator have emerged. The P5 implementation stage also runs according to the guidelines, but the integration of social studies learning, facilitator problems, and student conditions are challenges. Evaluation of each theme shows differences in methods, but overall it has been done well. Support from parents, school infrastructure, good communication, and financial support greatly assist the implementation of P5. However, there are obstacles such as suboptimal module preparation, less innovative classroom management, differences in facilitator age, technical constraints, dependence on gadgets, and variations in student interests.